Changes in physical fitness and body composition of pilot cadets before and after a process of directed flight preparation - Adam Prokopczyk; Zbigniew Wochyński (BMC, 2022)
Abstract Objectives The aim of the study was to check the changes in the level of physical fitness and body composition after a directed training process in cadets-pilots, in relation to control group. Material and methods The study involved 29 cadets studying at the Air Force Military Academy in Dęblin. Group A (study group)-second year pilots (n = 17), male, with an average age of 19.94 ± 1.3 years, studying to become an aircraft pilot, who realized 35-h directed training process based on the Aviation Synthetic Efficiency Test (ASET) and group B (control group)-second year in the field of ground navigation (n = 12), male, with an average age of 19.83 ± 1.27 years, completing the standard physical education process. In both groups, the fitness tests and physiological studies were conducted twice time: before starting the training process-study I; after the training process-study II. Fat mass (FM), fat-free mass (FFM), muscle mass (MM), total body water (TBW), extracellular water (ECW) and intracellular water (ICW) were measurement with using the bioimpedance method with using body composition analyzer the AKERN 101 type BIA 101SE. Results In group A in study II, fitness was at a good level, while in group B it was below the standard expected for pilots. There was statistically significant decrease in fat mass (FM) and increase in fat-free mass (FFM), muscle mass (MM), total body water (TBW) in group A compared to group B. In study II, group A showed no significant correlation between ASET and FM, FFM, MM, TBW while group B showed statistically significant correlations. Conclusions The results obtained in study II showed an increase in directed physical fitness in groups A and B, as measured by ASET. In both groups A and B, the training process decreased FM and increased FFM, MM, and TBW, but a greater effect of these changes was observed in group A.